2023
DOI: 10.1370/afm.2979
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Primary Care: Lessons Learned About Implementing Health Care Innovations During the COVID-19 Pandemic

Abstract: PURPOSE During the COVID-19 pandemic, telemedicine emerged as an important tool in primary care. Technology and policy-related challenges, however, revealed barriers to adoption and implementation. This report describes the findings from weekly and monthly surveys of primary care clinicians regarding telemedicine during the first 2 years of the pandemic.METHODS From March 2020 to March 2022, we conducted electronic surveys using convenience samples obtained through social networking and crowdsourcing. Unique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…We used an exploratory design to conduct mixed-methods analyses of data from multiple waves of the survey. The methods have been detailed elsewhere (Etz et al, 2023;Sullivan et al, 2023). Briefly, in March 2020, the Green Center began surveying primary care clinicians practicing family medicine, internal medicine, pediatrics, and other specialties in primary care settings.…”
Section: Methodsmentioning
confidence: 99%
“…We used an exploratory design to conduct mixed-methods analyses of data from multiple waves of the survey. The methods have been detailed elsewhere (Etz et al, 2023;Sullivan et al, 2023). Briefly, in March 2020, the Green Center began surveying primary care clinicians practicing family medicine, internal medicine, pediatrics, and other specialties in primary care settings.…”
Section: Methodsmentioning
confidence: 99%
“…eHealth technologies include mobile devices, telemedicine, artificial intelligence, and big data analytics [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The application of eHealth tools in PC leads to improvements at various levels, e.g., prevention, diagnostics, therapy, patient management, homecare for the elderly, risk prediction, clinical decision support, accuracy of diagnosis, optimization of healthcare resources, patient satisfaction of healthcare, equity of care, and health cost reduction [ 61 , 80 , 81 , 82 , 83 , 84 , 85 ]. However, there are limitations to the use of eHealth, such as existing socio-cultural norms, geographic inequalities in access to technology, and disparities in digital literacy [ 70 , 86 , 87 , 88 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the SARS-CoV-2 pandemic, there has been an increase in the use of eHealth solutions in rheumatology to ensure the continuity of care and the safety of patients and caregivers [ 82 , 89 , 90 ]. The retrospective study by Avouac J. et al demonstrated the effectiveness of telemedicine in the management of RA by rheumatologists [ 91 ].…”
Section: Introductionmentioning
confidence: 99%